Two isomorphous transition metal complexes displaying a coordinated tetrathionate unit: Bis(4,4′-dimethyl-2,2′-bipyridine- κ2 N,N′)(tetrathionato-κ2 S,S′)cadmium(II) dimethylformamide disolvate and the zinc(II) analogue - Harvey, M.A. (2013)
The isomorphous title compounds, [Tr(S4O6)(C 12H12N2)2]·2C 3H7NO (Tr = CdII and ZnII), consist of metal centres to which one tetrathionate and two 4,4′-dimethyl-2, 2′-bipyridine chelating ligands bind. The structures are completed by two symmetry-related dimethylformamide solvent molecules. Each metal-centred complex is bisected by a twofold axis running through the metal centre and halving the chelating tetrathionate dianion through the central S - S bond. The ancillary symmetry-related 4,4′-dimethyl-2,2′-bipyridine ligands act as chelates. This results in a distorted six-coordinate geometry, with similar Tr - O/N distances but central angles differing substantially from 90 and 180°. Both ligands are basically featureless from a geometric point of view, with torsion angles in both coordinated tetrathionate groups suggesting a trend linking metal size (covalent radius) and ligand 'openness'. Packing is directed by (C - H)aromatic⋯O bridges and π-π offset stacked interactions defining chains along [001], further linked by weaker (C - H)methyl⋯O bridges, some of them mediated by the dimethylformamide solvent molecules. © 2013 International Union of Crystallography.